Factors influencing nurse’s performance at KPJ Bandar Maharani / Noor Syakila Chu Mohd Alai - Chu Mohd Alai, Noor Syakila (Faculty of Business and Management, 2020)
In our current business world is where everything is all about high speed technology, tight competition, and gaining profit, one of the most significant contributors for the success of an organization is the level of the employee performance. Employee performance are one of the most important elements to ensure the company able to achieve its business goal. This purpose of this research is to explores few factors (competencies, mental health and high-performance work system) that will actually influence the employee performance. We want to understand these independent variables relationship strength with the derived variable. All the facts, data and figures in this research would definitely be important to be used by the organisation’s management to enhance the employee performance at KPJ Bandar Maharani Specialist Hospital. The respondent in this study are 103 from 140 staff that are currently working at the KPJ Bandar Maharani Specialist Hospital and they are consists of nursing staff. We collecting data from them by doing the survey using questionnaire that we distribute to them. This study took 4 months to finish. For the finding, the results indicate that competencies has the strongest impact towards employee performance at KPJ Bandar Maharani Specialist Hospital. This result is followed by high performance work system. Unlike competencies and high-performance work system, mental health have negative relationship with the employee performance and not significant towards employee performance at KPJ Bandar Maharani Specialist Hospital